2020
DOI: 10.4018/ijgcms.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Behavior of Professional and Non-Professional eSports Players in FIFA 19

Abstract: In traditional sports like soccer or tennis, experts benefit from better anticipation abilities compared to novices through a more efficient gaze behavior. For electronic sports (eSports), this area is rather unexplored, although quick decision making, which is linked to gaze behavior, is considered fundamental in eSports. In this study, the gaze behavior of professional and non-professional eSports players (n=21, 23.4 ± 3.3 years) was recorded via eye-tracking in the sports simulation FIFA 19. Number, duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similarly, three studies (Bickman et al, 2020, 2021; Wechsler et al, 2021) found that pro-gamers perform better than non-professionals due to better hand-eye coordination, mental strength, response time, game knowledge, and tactical comprehension. However, Sousa et al (2020) observed that pro-gamers’ faster response times are marred by less accuracy and impulsiveness.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, three studies (Bickman et al, 2020, 2021; Wechsler et al, 2021) found that pro-gamers perform better than non-professionals due to better hand-eye coordination, mental strength, response time, game knowledge, and tactical comprehension. However, Sousa et al (2020) observed that pro-gamers’ faster response times are marred by less accuracy and impulsiveness.…”
Section: Resultsmentioning
confidence: 92%
“…After comparing the results of three research studies by Jeong et al [ 9 ], Bickmann et al [ 10 ], and Koposov et al [ 11 ], we found that various esports genres require specific gaze control strategies. However, the characteristics of gaze movement, especially fixation on the multiplayer online battle arena (MOBA), remain unknown.…”
Section: Introductionmentioning
confidence: 78%
“…One research study that analyzed gaze movement during esports found out that highly skilled esports (real-time strategy games) players perform specific saccadic gaze movements [ 9 ]; however, that study did not evaluate the fixation characteristics present while playing esports. Additionally, the difference between the fixation gaze movement of professional esports players and non-professional esports players was compared by observing players of a soccer simulation video game called FIFA 19 [ 10 ]. Despite focusing on the fixation of gaze movement, no significant difference in the duration of the fixation time and the number of fixations of the professional esports players and non-professional esports players was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esports continues to experience development with various competitions emerging every year [15]. Regional, national and international competitions are held regularly to develop and introduce esports to the public [16].…”
Section: Introductionmentioning
confidence: 99%